Produksi Parthenogenetik Blastosis Mencit Sebagai Sumber Stem Cell - Rinendyaputri, Ratih; Nikmah, Uly Alfi (Central Basic Biomedical and Health Technology, 2013)
Embryonic Stem Cells (ESCs) is a one of source for pluripotent stem cell that capable to differentiate into various cell types. This has opened up opportunities utilization of embryos as a source of stem cells. However, the use of embryos as objects of research still has ethical constraints. Currently parthenogenetic embryo in the blastocyst stage is considered to be one of the alternative sources of ESC are